BIMBINGAN TEKNIS PENGEMBANGAN MATERI AJAR BAHASA INGGRIS DI MASA PANDEMI COVID-19: KETERAMPILAN MEMBACA MENGGUNAKAN LMS CANVAS INSTRUCTURE - Nurjati, Nunung; Bandjarjani, Wahju; Rahayu, Endah Yulia; Khabib, Samsul (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2021)
The COVID-19 pandemic has required every element of education, especially educators, to adapt, such as changing teaching methods from face-to-face (offline) learning to distance learning (online). Educators for all subjects, including English. Therefore, this community service program aims to contribute to the English Language Teachers' Association (MGMP) of State Senior High Schools and Vocational High Schools in Surabaya in the process of teaching English, particularly reading, during the COVID-19 pandemic by utilizing the Canvas Instructure platform through technical guidance for educators/teachers at State Senior High Schools and Vocational High Schools in Surabaya. The objectives of this technical guidance are: 1) to introduce the Canvas Instructure application platform as one of the Learning Management Systems (LMS) for teaching reading skills in English language classes; 2) to provide technical guidance to educators/teachers in developing English language teaching materials using the Canvas Instructure LMS learning platform; 3) to provide technical guidance to educators/teachers on practicing online learning using the Canvas Instructure LMS for the developed teaching materials; and 4) to monitor the implementation of Canvas Instructure in English language subjects, particularly reading skills, using the teaching materials developed by the school.